Polycrystalline cubic boron nitride composite materials
By using PCBN composite materials, combining the advantages of cBN particles and tungsten-rhenium alloy, the interface layer of Al is formed, which solves the problem of insufficient wear resistance and fracture toughness of FSW tools under high temperature and high load conditions, and achieves a longer life and efficient welding effect.
Patent Information
- Application Number
- CN202080080523.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-06
- Filing Date
- 2020-11-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-11-25
AI Technical Summary
Existing FSW tools have short service life under high temperature and high load conditions, insufficient wear resistance and fracture toughness, making it difficult to effectively weld high melting point alloys.
Using a PCBN composite material consisting of 60-90 volume % cubic boron nitride cBN particles and 10-40 volume % tungsten-rhenium alloy adhesive matrix material, the toughness and wear resistance of the material are enhanced by forming the boride or nitride interface layer of Al on the surface of the cBN particles.
It significantly improves the wear resistance and fracture toughness of FSW tools, extends the service life of the tools, and can stably weld high-melting alloys under high temperature and high load conditions.
Smart Images

Figure CN114728335B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a composite material comprising tungsten (W), rhenium (Re) and cubic boron nitride (cBN) particles formed together under high pressure and high temperature (HPHT) conditions. The present disclosure also relates to the use of the composite material as a probe or tool material for friction stir welding of steel, nickel alloys and other high melting point alloys, and to a probe having much higher performance than existing probes in terms of reduced wear and fracture. The present disclosure also relates to a method for making such a composite material and a probe comprising such a material. Background Art
[0002] Friction stir welding (FSW) is a technique in which a rotating tool is brought into forced contact with two adjacent workpieces to be joined and the rotation of the tool produces friction and viscous heating of the workpieces. Severe deformation occurs as mixing occurs along the plastic zone. As the plastic zone cools, the workpieces join along the weld joint. Since the workpieces remain in the solid phase, the process is technically a forging process rather than a welding process, nevertheless it is conventionally referred to as welding or friction stir welding and this convention is followed here.
[0003] In the case of FSW in low temperature metals, the entire tool / tool holder can be a single piece of formed tool steel, in which case it is often referred to as a "probe". In the case of tools used to weld higher temperature alloys (such as steels), the tool is often in two or more parts, with the end element that is in direct contact with the material being welded often referred to as a "puck" or "tool insert", and the remainder of the tool being a "tool holder" that securely holds the puck and fits into the FSW machine so that the tool puck and tool holder together constitute a "tool" or "tool assembly". The tool puck is often formed to form a shoulder and stirring pin, often with a reverse spiral cut into the surface so that during rotation it pulls the metal toward the pin and pushes the metal down into the hole formed by the pin.
[0004] Typically, a FSW operation includes several steps, such as:
[0005] a) The insertion step (also called penetration step), from the point when the tool contacts the workpiece to the point where the pin is fully embedded up to the shoulder in the heated and softened workpiece.
[0006] b) tool traverse, where the tool moves laterally along the line between the workpieces to be joined, and
[0007] c) The extraction step, when the tool is lifted or traversed out of the workpiece.
[0008] Tool traverse, which is the phase in which the weld is primarily formed, is usually performed under constant conditions; typically these conditions are rotation speed, penetration conditions, traverse speed, etc.
[0009] The FSW method was developed by The Welding Research Institute (TWI) in 1991 and is described in WO 93 / 10935. TWI has licensed the technology and although it is primarily used to weld together components made of aluminium (Al) alloys, it is also used for other low melting point metals such as copper (Cu), lead (Pb) and magnesium (Mg).
[0010] WO 2004 / 101205 claims FSW tools comprising, inter alia, superabrasive materials produced under high pressure and high temperature (HPHT) conditions. In particular, polycrystalline diamond (PCD) and polycrystalline boron nitride (PCBN) are claimed.
[0011] General Electric Company filed a patent application (US 2004 / 238599A1) for the use of tungsten-based refractory metal alloys for FSW of steel and other materials.
[0012] FSW is a well established method for joining metals. However, it is currently typically only suitable for metals with relatively low melting points because of the requirement that the FSW tool or probe material retains its essential properties at the joining temperature and does not chemically interact with the metal being joined. For this reason, it is not feasible to join steel and other high melting point metals by FSW using a steel probe, such as is used in the case of lower melting point metals such as Al & Cu.
[0013] The recent drive is to develop FSW probes using materials that retain their basic properties and form at temperatures above 1000°C in an iron-containing environment so that FSW joining of steel and other high melting point metals is technically and commercially feasible. It is difficult to develop suitable tools, at least in part due to the temperature, but also due to the loads to which the tools are subjected during the process. It has generally been found that these tools have a limited life cycle. In addition, these tools are typically made of expensive materials that are difficult to form, so the tools are expensive. Currently, the life of such tools is typically measured in terms of the number of meters of welding per tool, and the cost of using the tool is measured in terms of $, USD per meter, dividing the tool cost by the tool life in meters. Although many benefits of friction stir welding in steel have been known since about 2000, its use is very limited because currently available tools are considered expensive, unreliable and have a limited life.
[0014] For example, the use of polycrystalline cubic boron nitride (PCBN) produced by the HPHT method as a probe material has been described in the art. There is also a lot of research on the use of W, Re, Mo, including their alloys and other refractory metals. Both approaches (PCBN and refractory metals) have different disadvantages:
[0015] Although PCBN is far more wear resistant than required for this application, its fracture toughness is lower than ideal. This application involves penetrating the probe into the workpiece at the joint between the two pieces when the workpiece is initially cold and the contact point between the workpiece and the tool is relatively small. This step therefore involves high forces and rapid heating, and can severely stress and damage the tool. During the subsequent traverse, when the tool also rotates, the tool is also subject to large cyclic forces, which can drive crack propagation.
[0016] Although refractory metals such as W, Mo and Re have sufficient fracture toughness, they lack the wear resistance required for commercially viable probes, and their main failure mechanism is wear. More importantly, probes made of such metals tend to deform in shape during application.
[0017] There has been a long-felt need for a material that combines the toughness and strength of W, Mo or Re with the enhanced wear resistance of PCBN, while retaining the essential chemical inertness and form required during FSW applications. Summary of the invention
[0018] In a first aspect of the present invention, a polycrystalline cubic boron nitride (PCBN) composite material is provided, which consists of: 60-90 volume % cubic boron nitride (cBN) particles and 40-10 volume % of a binder matrix material, wherein the cBN particles are dispersed in the binder matrix material, wherein the cBN particles have an average grain size in the range of 8 to 20 μm, wherein the binder matrix material comprises 90-99 weight % of an alloy of refractory metals tungsten (W) and rhenium (Re), and further comprises aluminum (Al) in non-oxide form, wherein the binder phase comprises an interface layer on the cBN grains, wherein the interface layer comprises a boride or nitride of Al, wherein the aluminum (Al) is present in an amount of 2-10 weight % of the binder matrix material, and wherein the interface layer has an average thickness in the range of 100-250 nm.
[0019] Optionally, the interface layer covers at least 50% of the surface of the cBN grains.
[0020] Optionally, the interface layer is a reaction layer comprising Al, B and N, and comprises aluminum nitride and / or aluminum boride.
[0021] The composition of the reactive layer may vary throughout its thickness.
[0022] Optionally, the interfacial layer comprising Al has an average thickness of 170-190 nm, measured using the method described herein.
[0023] Optionally, the total oxygen content of the composite material is less than 3%, preferably less than 2%, preferably less than 1%, preferably less than 0.5%, preferably less than 0.3%, measured as described herein.
[0024] The PCBN material may comprise 70 volume % cBN particles and 30 volume % binder matrix. Preferably, the PCBN composite material comprises 65-75 volume % cBN particles and 25-35 volume % binder matrix.
[0025] Optionally, the composition of the tungsten-rhenium alloy is in the following range: 72 wt% to 77 wt% tungsten (W) and correspondingly 28 wt% to 23 wt% Re. The tungsten-rhenium alloy may contain 90 wt% tungsten and 10 wt% rhenium, or 80 wt% tungsten and 20 wt% rhenium, or 74 wt% tungsten and 26 wt% rhenium, or 70 wt% tungsten and 30 wt% rhenium, or 60 wt% tungsten and 40 wt% rhenium, or 50 wt% tungsten and 50 wt% rhenium.
[0026] Optionally, the grains of the W-Re alloy have an average grain size ranging from 3 to 5 μm, measured as described herein.
[0027] The PCBN material may comprise a rhenium-aluminum alloy in a binder matrix material.
[0028] The PCBN composite may further comprise WC impurities within the binder matrix material, the impurity being present in an amount less than 1 wt % of the PCBN composite.
[0029] The PCBN composite material may have a Young's modulus of 500 to 560 GPa, based on measurements of the velocity of sound and calculated as described herein.
[0030] The cBN particles may have a sharpness ranging between 0.40 and 0.70, wherein the sharpness is measured as described herein.
[0031] The PCBN composite material may have a sonic velocity between 8 and 9 km / s, measured as described herein.
[0032] In a second aspect of the present invention, a method for manufacturing a polycrystalline cubic boron nitride (PCBN) composite material is provided, the method comprising the following steps:
[0033] - providing a matrix precursor powder comprising the refractory metals tungsten (W) and rhenium (Re) and which further comprises 2 to 10 wt.% of Al in non-oxide form;
[0034] - providing cubic boron nitride (cBN) powder comprising cBN particles;
[0035] - Mixing matrix precursor powder and cBN powder;
[0036] - compacting the mixed matrix precursor powder and cBN powder to form a green body;
[0037] - degassing the green body at a temperature of 800° C. to 1150° C.;
[0038] - sintering the green body at a temperature of 1300°C to 1600°C and a pressure of at least 3.5 GPa to form the PCBN composite material according to the first aspect of the invention.
[0039] Optionally, the matrix precursor powder comprises separate particles of W, Re and Al. Alternatively, the matrix precursor powder comprises particles of both W and Re, either pre-alloyed or as separate phases, such as one encapsulating the other.
[0040] The step of mixing may include mixing the matrix precursor powder and the cBN powder using a mixing container that does not contain exposed metal or WC surfaces.
[0041] The step of mixing may include mixing the matrix precursor powder and the cBN powder in a polymer or polymer coated mixing tank.
[0042] The step of mixing may include mixing the matrix precursor powder and the cBN powder using a mixer with blades, wherein the mixing blades of the mixer are coated with a polymer. Alternatively, the step of mixing may include mixing the matrix precursor powder and the cBN powder using a bladeless mixer.
[0043] Optionally, the method comprises the following sub-steps:
[0044] - Add cBN and aluminum powders together;
[0045] - Mix in a container at 800 rpm for 2 minutes, then at 1200 rpm for 2 minutes;
[0046] - Add half of the tungsten-rhenium powder to the cBN and aluminum powders;
[0047] - Mix in a container at 800 rpm for 2 minutes, then at 1200 rpm for 2 minutes;
[0048] - adding the remaining half of the tungsten-rhenium powder to the cBN and aluminum powders; and
[0049] - Mix in container at 800 rpm for 2 minutes and then at 1200 rpm for 2 minutes.
[0050] Optionally, the step of sintering comprises sintering at a temperature of 1500°C.
[0051] Optionally, the step of sintering comprises sintering at a pressure in the range of 4.0-6.0 GPa.
[0052] Optionally, the adhesive matrix material comprises 98 wt % of the tungsten-rhenium alloy and 2 wt % of the aluminum compound.
[0053] In a third aspect of the invention there is provided a friction stir welding tool for friction stir welding ferrous alloys, the tool rotating in operation about an axis of rotation, the tool comprising a shoulder and a stirring pin extending from an apex to the shoulder, the tool having in operation an average wear rate of less than 3 μm / meter of weld, the wear rate measured as described herein. Preferably, the friction stir welding tool comprises a PCBN composite material according to the first aspect of the invention. Other optional and / or preferred features of the third aspect of the invention are also provided in claims 2 to 16.
[0054] In a fourth aspect of the invention, there is provided a friction stir welding tool for friction stir welding ferrous alloys, the tool rotating in operation about an axis of rotation, the tool comprising a shoulder and a stirring pin extending from an apex to the shoulder, the tool having an average wear rate ratio of less than 1 μm / (m.mm) in operation, which is 1 μm per meter of weld per mm of pin length. Preferably, the friction stir welding tool comprises a PCBN composite material according to the first aspect of the invention. Other optional and / or preferred features of the fourth aspect of the invention are also provided in claims 2 to 16.
[0055] In a fifth aspect of the invention there is provided a friction stir welding tool for friction stir welding ferrous alloys, the tool rotating in operation about an axis of rotation, the tool comprising a shoulder and a stirring pin extending from an apex to the shoulder, the tool being manufactured and configured in operation to withstand more than 10 penetrations without brittle failure, visible under an optical microscope, the wear rate being measured as described herein. Preferably, the friction stir welding tool comprises a PCBN composite material according to the first aspect of the invention. Other optional and / or preferred features of the fifth aspect of the invention are also provided in claims 2 to 16.
[0056] In a sixth aspect of the invention, there is provided a friction stir welding tool for friction stir welding ferrous alloys, the tool rotating about a rotation axis during operation, the tool comprising a shoulder and a stirring pin extending from a vertex to the shoulder, the tool further comprising a polycrystalline cubic boron nitride PCBN material according to the first aspect of the invention. Preferably, the friction stir welding tool comprises a PCBN composite material according to the first aspect of the invention. Other optional and / or preferred features of the sixth aspect of the invention are also provided in claims 2 to 16.
[0057] The pin length is typically 95% of the expected depth of the weld, so that for a full thickness butt weld with no root defects in 6mm thick steel, the pin length is 5.7mm. Many FSW process parameters scale with pin length in some manner, as described below. For convenience and because it is a standard size used for tool development and testing, the discussion centers on tools for 6mm welding, i.e., with a pin length of 5.7mm, with scaling factors used to account for other tool sizes given subsequently.
[0058] The tool insert of the present invention is capable of withstanding at least 10, 20, 30, 50, 100 penetrations without incurring any brittle damage, such as chipping or cracking visible under an optical microscope.
[0059] Optionally, the tool insert of the present invention has a low average wear rate ratio in use. The wear rate (WR, μm / m) is measured as the average wear (in μm) measured in the axial direction on the central area of the tool insert (the apex of the tool), up to a diameter equal to 1.5 times the pin length L (for example, for a 5.7 mm pin, up to a diameter of 1.5×L=1.5×5.7 mm=8.55 mm), and is given as a value per meter of test weld completed. Since the wear is not concave when viewed axially from the tip, this is equivalent to having the total volume of material lost from the tool insert in a cylinder of diameter 1.5L, converting this to a cylinder of diameter 1.5L, the average wear is then the length of this cylinder, and the wear rate WR is this value divided by the total weld length.
[0060] Since the exact conditions on the tool vary with the pin size, the wear rate and threshold achieved by the present invention also vary with the pin size of the tool insert. Therefore, in order to provide a value relevant to all tool sizes, the wear rate WR is divided by the pin length to give the wear rate ratio (WRR, μm / {m.mm}). The wear rate ratio is therefore the ratio of the wear rate measured in μm divided by the pin length in mm per meter of weld passed. As an example, the material of the present invention may exhibit the following wear rate: <0.3 μm / meter of 6 mm deep weld, resulting in a WRR of 0.3 / 5.7=0.053.
[0061] Therefore, the average wear rate ratio is preferably less than 1.0 μm / (m.mm), and preferably less than 0.5, 0.2, 0.1, 0.05 μm / (m.mm). BRIEF DESCRIPTION OF THE DRAWINGS
[0062] The present invention will now be described in more detail, by way of example only, with reference to the accompanying drawings, in which:
[0063] Figure 1 shows a partial side view of a friction stir welding tool;
[0064] Figure 2 Yes Figure 1 A side view of a tool assembly including a tool, a tool holder, and a locking collar securing the tool to the tool holder;
[0065] Figure 3 is the X-ray diffraction trace of the tool material showing the main phase;
[0066] Figure 4 yes Figure 3 A magnified view of the X-ray diffraction trace;
[0067] Figure 5 is a scanning electron microscopy (SEM) micrograph of the tool microstructure at 500X magnification;
[0068] Figure 6 is a SEM micrograph of the tool microstructure at 1000X magnification;
[0069] Figure 7 Schematic diagram of how to measure the distance between similar cBN grains;
[0070] Figure 8 is a graph showing the cBN grain size distribution of the tool material;
[0071] Fig. 9 is a graph showing the distance between cBN grains of the tool material, expressed as the nearest neighbor distance d (μm).
[0072] Fig.10 is a SEM micrograph showing the microstructure of a known TiN / Al PCBN material at 2000X magnification for comparison with the tool microstructure;
[0073] Fig.11 It is shown Fig.16 Coordinate diagram of cBN grain size distribution of TiN / Al PCBN material;
[0074] Fig.12 is a graph showing the distance between cBN grains of TiN / Al PCBN material, expressed as the nearest neighbor distance d (μm);
[0075] Fig.13 is a SEM micrograph of cBN grains within the tool microstructure at 15000X magnification;
[0076] Fig.14 yes Fig.13 a manipulated copy of an SEM micrograph of , showing a reaction layer at least partially covering the cBN particles;
[0077] Fig.15 yes Fig.13 Manipulated copy of the SEM micrograph showing only the reaction layer, extracted for the purpose of calculating the reaction layer thickness;
[0078] Fig.16 is a graph showing the thickness distribution of the reaction layer;
[0079] Fig.17 is a manipulated SEM micrograph of a Knoop hardness indentation at 1000X magnification; and
[0080] Fig.18 is a flow chart illustrating an exemplary method of manufacturing sintered PCBN material;
[0081] Fig.19 is shown with additional, optional sub-steps Fig.18 A flowchart of an exemplary method; and
[0082] Fig. 20 It is a graph showing the grain sharpness of cBN grains in the sintered material. DETAILED DESCRIPTION
[0083] Geometry
[0084] Refer to the attached Figure 1 and 2 , a FSW tool insert is generally indicated at 10. The tool insert 10 has an axis of rotation 12 about which it rotates during FSW. (Note that the axis of rotation is not an axis of rotational symmetry, largely due to the asymmetrical thread pattern machined into the tool insert). In use, the tool insert 10 is shrink fit into a tool holder 14. A locking collar 16 secures the tool insert 10 in place on the tool holder 14. Note that this is an example of a common type of tool holder, but the present invention is independent of the type of tool holder used.
[0085] The tool insert 10 comprises a stirring pin 18, a shoulder 20 and a body portion (not shown), all of which are axially aligned with each other. The stirring pin 18, shoulder 20 and body portion are all integrally formed with each other.
[0086] The stirring pin 18 extends from a circular vertex 22 to a shoulder 20. In this embodiment, the shoulder 20 is substantially cylindrical and has a larger diameter than the circular bottom of the stirring pin 18. The stirring pin 18 has an inscribed spiral feature extending downward from the vertex 22 to the shoulder 20. Therefore, the profile of the stirring pin 18 is generally conical. The spiral has a planar path 24 facing the axial direction. In use, the rotation of the tool causes the spiral to drive the workpiece material from the edge of the shoulder 22 to the center, and then downward along the length of the stirring pin 18, forcing the workpiece material to circulate in the stirring area and fill the gap formed by the pin when the tool is traversed. It is understood that this circulation will promote a uniform microstructure in the resulting weld. The working surface 26 of the tool insert 10 faces radially.
[0087] Several flats 28 (tri-flats) are provided in the spiral. Each flat 28 is an edge chamfer of the planar path 24. In this example, three groups of flats 28 are provided, each group having three flats 28, resulting in a total of nine flats 28 for this particular tool 10. The groups are spaced about 120 degrees around the axis of rotation 12. Within each group, the flats 28 are spaced axially on the spiral, i.e. spaced along the axis of rotation 12, but still on the spiral.
[0088] The shoulder 20 extends axially to conform to the body portion. The body portion is configured to couple with a tool holder 14. Examples of tool holders and correspondingly shaped tools are provided in the applicant's co-pending patent application GB1819835.8. For example, the body portion may have a hexagonal transverse cross section.
[0089] composition
[0090] In terms of materials, example compositions of tool materials according to the present invention are provided in Table 1.
[0091] Table 1
[0092]
[0093] Using X-ray diffraction (XRD), such as Figure 3 and 4 As shown, the main phases identified in the composite are cBN and W-Re alloy. However, peaks of Re-Al alloy and AlN are also observed.
[0094] Use scanning electron microscopy (SEM) to visually capture the microstructure—see Figure 5 and 6 The microstructure was then characterized. The grain size and the distance between cBN grains, referred to herein as the "neighbor distance d," were measured from SEM micrographs taken at 500X and 1000X magnification. Figure 7 and explained further below.
[0095] The neighbor distance is similar to the expression "binder mean free path", which is a term widely used in the literature about carbides and is measured after the material has cooled to room temperature. It is probably the most important single parameter for characterizing the microstructure of the binder. It is a measure of the binder thickness and depends on the binder composition and particle size. It is nominally based on the average spacing of the particles, assuming that all particles are separated from each other by a binder layer, and taking into account the presence of continuous carbide particles and the absence of any binder phase between them (Exner, HE, Gurland, J., POWDER METALLURGY, 13 (1970) 20-31, "A review of parameters influencing some mechanical properties of tungstencarbide-cobalt alloys").
[0096] Used from Jeol TM Images were captured using a JSM 6610 series scanning electron microscope. The sample was placed at a working distance of 7 mm and the accelerating voltage was set to 10 kV. The grain size was measured using ImageJ image analysis software and the “Watershed” image processing technique.
[0097] Briefly, grain size is measured using the following steps:
[0098] - forming a binary value of the SEM image;
[0099] - Apply grid lines at 10 micron spacing across the image; and
[0100] -Measure grain size along the line.
[0101] The grain size was obtained from 33 micrographs and more than 30,000 grain size samples were measured in total. The cBN grain size is expressed as the equivalent circular diameter (ECD). The results are shown in Figure 8 Medium. The average cBN grain size is 9 μm.
[0102] The distance between similar grains, i.e. the nearest neighbor distance, was also analyzed and the results are shown in Fig. 9 This shows that the distance between cBN grains is in the range of 0.1 to 2.0 μm.
[0103] For comparison purposes and to understand the numerical limits of the neighbor distance, a second cBN material (coded Ct1291) was analyzed. The composition of Ct1291 is provided in Table 2.
[0104] Table 2
[0105]
[0106] The microstructure, cBN grain size distribution and nearest neighbor distance of Ct1291 are Fig.10 , 11 and 12. For an average grain size of 1 to 2 μm, the average nearest neighbor distance d is 0.3 μm, and the individual results vary between 0.1 and 2.0 μm.
[0107] Returning to the sintered tool material, due to the presence of aluminum in the precursor powder, the cBN grains were found to have aluminum nitride and / or aluminum diboride (AlN / AlB 2 ) of the composite. The thickness of the reaction layer (the measurement of which is described in more detail below) reflects the HPHT sintering conditions used. The improved toughness and wear resistance of the composite are attributed to this reaction layer. It is proposed that it is the reaction layer that makes the composite particularly suitable for FSW, as described in more detail below.
[0108] The benefit of this coating is that it is believed to enhance the mechanical properties of the sintered material. By ensuring a strong bond between the cBN particles and the W-Re binder, it can enhance the toughness of the material (the cBN supports the W-Re) and wear resistance (the cBN is retained and supported by the W-Re). It is also believed to stop intergranular cracking.
[0109] The coating can also reduce the thermal conductivity of the composite. The thermal conductivity is determined by the volume fraction of cBN in the material, as this has a much higher thermal conductivity than the W-Re binder. However, the effect of cBN on thermal conductivity can be modulated by using smaller cBN particles, and by coatings on the cBN particles, thereby inducing poorer thermal connectivity between them (different phononic structures in the interface layer). Using the tool can result in better heating of the workpiece, as less heat is conducted away by the tool, as it has a lower thermal conductivity. It is worth noting that the coating formed by the Al reaction can be more chemically disordered than any previous metallic coating.
[0110] For analytical purposes, in e.g. Fig.13 and Fig.14 The reaction layer was identified in the image and visually separated from the cBN grains using software (see, for example, Fig.15 ) so that the thickness of the reaction layer can be measured.
[0111] like Fig.16 As shown, the average thickness of the reaction layer is 180 nm, with individual results ranging from 0.1 μm to 1.6 μm.
[0112] Young's modulus and speed of sound
[0113] After measuring the longitudinal sound velocity and calculating the density of each tool, the Young's modulus was calculated for each of the three batches of test tools. The density of the tools was calculated using Archimedean principle.
[0114] Young's modulus Y = ρv 2
[0115] (where ρ is the density of the solid and v is the speed of sound)
[0116] Table 3 shows the results.
[0117] Table 3
[0118]
[0119] Knoop hardness
[0120] The Knoop microhardness of the material was measured under a load of 1 kg and a dwell time of 15 seconds on a mirror-polished surface. Fig.17 At least 16 indentations are measured to obtain the average microhardness of the material.
[0121] Knoop hardness
[0122] (where HK is the Knoop hardness in GPa, P is the applied load in Kg, and d is the length of the diagonal)
[0123] The Knoop hardness results are provided in Table 4.
[0124] Table 4
[0125]
[0126]
[0127] The average Knoop hardness of the tool material was 16.9 ± 3.5 GPa. The variability in the results is inherent to this type of composite material and because the indentation is either a binder-dominated or cBN-dominated region.
[0128] Manufacturing method
[0129] Fig.18 and 19 An exemplary method for producing sintered tool PCBN material is shown. Fig.19 Shown with Fig.18 Same process, but with an optional additional mixing sub-step. The following numbers correspond to the additional Fig.18 and 19 Number.
[0130] S1. Provide matrix precursor powder in a volume percent ratio of cBN to binder of 70:30.
[0131] S2. cBN powder is added to W-Re and Al (metallic) binder powder. The average size of the cBN particles in the cBN powder is between 8 and 20 μm. The size distribution of the cBN can be monomodal or multimodal (including bimodal). The binder has a composition: 98 wt% W-Re and 2 wt% Al. The amount of aluminum added takes into account the estimated surface area of the cBN grains to ensure at least partial coverage.
[0132] The ratio of tungsten to rhenium in the W—Re mixture is optionally any one of the following ratios: 95:5, 90:10, 80:20, 74:26, 70:30, 60:40, 50:50.
[0133] Mix the powders in the following order.
[0134] S3. The cBN powder and the aluminum powder were mixed at 800 rpm for 2 minutes and then at 1200 rpm for 2 minutes;
[0135] S4. Then half of the W-Re powder mixture is added to the cBN powder;
[0136] S5. The powder was mixed at 800 rpm for 2 minutes and then at 1200 rpm for 2 minutes;
[0137] S6. The remaining W-Re powder mixture is then added to the cBN-W-Re mixture;
[0138] S7. The powder was mixed at 800 rpm for 2 minutes and then at 1200 rpm for 2 minutes.
[0139] Using SpeedMixer TM The precursor powders are mixed together using the SpeedMixer TM It is a bladeless dry powder mixer. The advantage of using this approach is that, unlike attrition milling, impurities from grinding media are avoided. Milling is not only conventionally used to break matrix precursor particles to a desired size, but also closely mixes and disperses matrix precursor particles and cBN particles. Usually milling is performed with tungsten carbide balls. The sintered PCBN material produced using milling can contain up to 8% by weight of tungsten carbide, typically 2% by weight to 6% by weight of tungsten carbide. It is known that these particles have an adverse effect on the properties of PCBN materials, particularly in applications such as hard component turning. In addition, the tungsten carbide intake during milling is uncontrolled, so different batches can contain different tungsten carbide amounts, and have different size distributions, thereby causing the sintered PCBN material to have unpredictable performance when used in tool applications.
[0140] Another advantage of this approach is that there is no crushing of the cBN grains. The effect is that the sharpness of the sintered cBN grains within the composite is greater than those grains sintered after milling. Sharpness can also enhance the integrity and toughness of the material. Sharpness is explained in more detail below.
[0141] Additionally, the bladeless mixing approach reduces the reactivity of the precursor powders, making them safer to handle. Finally, with higher purity precursor powders (significantly less contamination), the sintered PCBN is stronger.
[0142] Grain sharpness can be used as an indicator of the mixing route used, because the sharpness of cBN grains before and after sintering is mainly determined by the mixing route. Using a bladeless dry mixer to mix produces cBN grains with different grain sharpness compared to those formed by milling. More details on how to calculate grain sharpness will be provided later. More than 24,000 grains were analyzed from SEM micrographs taken at 500X magnification. ImageJ software was used for analysis. The average circularity was 0.62 ± 0.1. Fig. 20 The scatter of results is provided in . Small grain sizes are not accurately measured, here less than 1 micron, so circularity is based on grain sizes above 1 micron.
[0143] It is contemplated that ultrasonic mixing or dry acoustic mixing in a solvent may be used as an alternative to the above-described bladeless mixing. Thus, the level of impurities found in the sintered composite is less than 4 wt %, and may be less than 3 wt %, or 2 wt %, or 1 wt %. Even if tungsten carbide impurities can be avoided, trace amounts of iron impurities may still be present from the original precursor powder.
[0144] Compared to milling, bladeless mixing, ultrasonic mixing, and dry acoustic mixing all provide faster and more efficient mixing methods, with the benefit that the time used to prepare sintered PCBN material is greatly reduced.
[0145] S8. The mixed powder is then pressed into a green body. Pre-compaction is necessary to ensure minimal volume change during final sintering. If the density is not maximized before sintering, the increased shrinkage upon sintering may result in a decrease in pressure, leading to conversion of cBN to hexagonal boron nitride (hBN) and cracking of the sample.
[0146] S9. The green body is introduced into a cladding (also called a "can") formed of a refractory metal such as niobium. The can containing the mixture is then placed in a vacuum furnace (Torvac) and subjected to high temperature conditions under vacuum. This step removes excess oxygen from the mixture and subsequently aids sintering. Degassing is performed at a temperature of 900°C to 1150°C. Degassing is an important factor in achieving high density in the finished composite material. In the absence of degassing, the sintering quality is poor. Degassing is usually performed overnight for a minimum of 8 hours, depending on the amount of material being degassed.
[0147] S10. After degassing, the canister may be sealed while it is still in the degassed condition, and then the canister containing the mixture is placed in a HPHT capsule.
[0148] S11. The can containing the mixture is then subjected to high pressure and high temperature conditions for complete sintering. The sintering temperature is between 1300°C and 1600°C, and the pressure is at least 3.5 GPa. The sintering pressure is generally in the range of 4.0 to 6.0 GPa, preferably 5.0 to 5.5 GPa. The sintering temperature is preferably about 1500°C. Complete sintering forms a polycrystalline material comprising cBN particles dispersed in a matrix material.
[0149] After the sintering process, the pressure is gradually reduced to ambient conditions. The fully sintered composite material is allowed to cool to room temperature and then formed into a tool suitable for friction stir welding.
[0150] Oxygen Levels
[0151] Oxygen is detrimental to the properties of the tool insert. Al additions are beneficial to tool properties unless they are in the form of oxides. Likewise, oxygen contamination in the source material used to sinter the tool insert or exposing the tool to atmospheric oxygen when the tool is at operating temperature (>600°C) is also detrimental.
[0152] As with many other materials, measuring oxygen in PCBN requires care to avoid atmospheric contamination affecting the measurement. This can be achieved by energy dispersive X-ray spectroscopy (EDS) in a SEM, or by atomic ionization techniques.
[0153] Preferably, the total oxygen content of the composite material is less than 3%, preferably less than 2%, preferably less than 1%, preferably less than 0.5%, preferably less than 0.3%.
[0154] Test Method
[0155] Thickness measurement method for reactive layers
[0156] Use the following steps:
[0157] - Calibrate SEM images with scale bar;
[0158] - Use grayscale threshold recognition technology to identify the reaction layer;
[0159] - Binarize the image to highlight only the reaction layer attached to the cBN grains;
[0160] - applying a grid with 100 nm spacing in horizontal and vertical directions; and
[0161] -Measure thickness in two directions.
[0162] XRD process for peak ratio calculation
[0163] Under the following conditions, in Philips Xpert TM XRD studies were carried out on an X-ray diffractometer.
[0164] Table 5
[0165]
[0166] The ratio of the areas under the XRD peaks was calculated and the composition of the material was determined as shown in the table below.
[0167] Table 6
[0168] Compound AlN <![CDATA[AlRe 2 ]]> <![CDATA[AlRe 2 ]]> W Peak position (2θ°) 54.039 21.12 36.58 68.96 ratio AlN / CBN(%) <![CDATA[AlRe 2 / CBN]]> <![CDATA[AlRe 2 / CBN]]> W / CBN Reflective surface (002) (002) (011) (200) batch Batch-3 6.087855 6.640826873 20.41344 256.8992 Batch-2 0 8.163265306 7.544836 198.5158 Batch-1 0 0 13.28244 265.1908
[0169] Sound velocity measurement
[0170] Scanning acoustic microscopy (SAM) is used as a non-destructive method to detect and quantify defects in components before failure and to determine the acoustic velocity of the material.
[0171] The KSI v400 from Kramer Sonic Industries GmbH was used under the following conditions: TM SAM Machine:
[0172] Table 7
[0173] Sample size 25mm diameter, 25mm height Transducer location 2mm above the sample Wave speed 8642m / sec Measuring peak Top peak and back peak
[0174] Performance testing of tool inserts
[0175] Optionally, the tool has a low average wear rate ratio in use and is capable of withstanding a large number of penetration cycles without failure. The wear rate is measured as follows: the average wear rate is measured in the axial direction over the central area of the tool (the apex of the tool) to a diameter equal to the pin length and given as a value per meter of weld completed (e.g., divided by the length in meters of the test weld).
[0176] In characterizing tool performance, tools typically fail by one of two mechanisms, either wear resulting in significant loss of the tool's surface features (which drive metal down the pin to fill the void behind the tool as the pin traverses), or cracks that significantly degrade the tool's shape. Regardless of their initial origin, cracks typically develop under cyclic loading on the pin, eventually surrounding the base of the pin and causing the pin to shear off. Two crack sources have been identified, the primary one being high localized loads during penetration of the tool into the cold workpiece, and the second being poor seating of the tool in the tool holder. Therefore, the key parameters for tool life are:
[0177] Meters of welds before wear or fracture significantly and adversely affects weld quality. As mentioned previously, unless cracking interferes, the main issue here is the wear rate of the tool, and this is largely a property of the tool material. Since life testing of high performance tools is very expensive, a more practical test is to measure the wear rate over a given weld length, and this method is adopted here.
[0178] The number of penetrations into the workpiece, which may lead to cracking and thus failure. The forces acting during penetration can be mitigated by several known methods, such as preheating the workpiece for drilling the pilot hole. For the purpose of the test, penetration was done by penetrating the workpiece at room temperature without any special preparation or mitigation techniques for penetration.
[0179] Standardized FSW test for wear rate measurement
[0180] First, the wear rate test of a tool designed for 6 mm welding will be described, and then normalized for other tool sizes. The pin length of the tool is 95% of the depth of the expected weld, so for a 6 mm weld depth (D W ), the pin length of the tool (L) is 5.7 mm. The reference to the 6 mm tool refers to the expected weld depth D W , and therefore refers to a tool with a 5.7 mm pin.
[0181] The tool is mounted in a tool holder which is mounted into a milling machine suitable for applying the conditions for FSW. Conditions for testing a tool suitable for making 6mm deep welds are described primarily, but methods for scaling the method to other tool sizes are then given.
[0182] The workpiece was DH 36 steel. For simplicity, the test did not require two separate plates prior to welding, the test could be carried out in the area of a single plate, and the plate thickness was typically oversized by about 8 mm to avoid this being a critical factor in the test. The tool was tilted slightly throughout the test so that the pin pointed forward in the traverse direction at an angle of 0-5 degrees (typically 2 degrees).
[0183] A shielding gas of Ar was maintained in place during the test to avoid contact of the tool and workpiece with atmospheric oxygen during welding.
[0184] The key variables in FSW are (always in standard SI units):
[0185] L = Pin length (m)
[0186] ν=traverse speed (m / s)
[0187] ω = rotational speed of the tool
[0188] Three forces are applied to drive this behavior.
[0189] F A =Axial load (N)
[0190] F T = Transverse force (N)
[0191] F R = Rotational force (N·m)
[0192] The rotation rate of the tool is varied during the start of the process.
[0193] Insertion: The cold tool was rotated at 800 rpm and approached to the workpiece in a slow steady approach so that penetration took approximately 90-120 seconds to complete.
[0194] Traverse: The tool rotation rate was reduced to 200 rpm and the tool was traversed at 0.3 m / min or 0.005 m / s.
[0195] Extraction: Tool rotation continues for traverse. Maintain argon purge gas until the tool has cooled sufficiently to avoid risk of oxidation. This point needs to be emphasized - oxidation of the tool insert caused by using an ineffective inert gas (typically argon) purge during the cool down period after extraction can lead to significantly increased wear rates, perhaps by more than a factor of 10.
[0196] Measuring the number of penetrations (penetration life)
[0197] The tool is inserted as described above, then the minimum value of 1m is traversed, then extracted and repeated, and the total number of insertions is counted. The use of techniques such as preheating the workpiece or drilling a coaxial or deviated guide hole will not alleviate the piercing force, but is initially carried out on the plane surface of the workpiece at room temperature. More typically, in order to combine the piercing test and the wear test, the welding test for wear described below is completed in a cross section of about 2 meters. The precise conditions of piercing can be optimized using the ordinary skills of those skilled in the art to minimize the impact load (combination of force and thermal shock from frictional heating) on the tool tip, so that the piercing life of the tool is maximized.
[0198] The tool insert of the present invention is capable of withstanding at least 10, 20, 30, 50, 100 penetrations without any brittle damage, such as chipping or cracking, visible on the tool insert under an optical microscope.
[0199] In contrast, prior art tools are known to fail after the first penetration, particularly when penetration relief is not used, and typically will not withstand more than five penetrations.
[0200] Measure tool wear rate.
[0201] Typically, the highest wear rates of the tool insert are seen at the base of the pin where the pin bends into the shoulder of the tool insert. In order to measure the wear rate and provide comparisons between tool inserts, a protocol needs to be established as this has not been measured previously reported in a systematic manner and because most FSW tools to date fail rapidly in steel.
[0202] The wear rate is a function of certain other test parameters, so other conditions of the test need to be specified or optimized. Here are the specified perceptible start-up parameters, but a person of ordinary skill in the art can achieve small improvements in tool insert life by optimizing the parameters, and it is expected that such optimizations will be used in testing. The tool traverse, which is the main stage in forming the weld and generating wear, is carried out under constant conditions; the conditions involve pin length, tool rotation speed and traverse speed. If the machine traverses accurately to the workpiece, the process can be run in position control, however, in order to allow for small distortions of the workpiece, those skilled in the art will understand that it is generally more appropriate to control the applied force, which allows responsiveness to local workpiece changes. In any case, once the tool traverse is started, these conditions should remain essentially constant for the duration of the traverse until near the end of the weld. These conditions are considered to be "steady-state operation" in this article.
[0203] The following scheme has been found to be robust and reliable. The goal is to measure the material loss due to wear on the tool and provide this data as an average linear wear rate per meter of weld length. In order to maximize the sensitivity of the test, the measurement is restricted to a circle around the axis of rotation of the tool insert with a diameter equal to 1.5 times the pin length. In principle, there are several ways to measure the volume loss from the tool due to wear, but since the tool does not have recessed features, the simplest method is to use a 3D optical microscope, in which images are taken of the tool tip around the axis of rotation before use and periodically during the test. From the 3D image, a subtraction image can be generated, which shows the height difference between the varying surfaces in the image that vary with tool use, and from this the height change in a direction parallel to the axis of rotation is calculated at each point in the image, within a circle defined by a diameter equal to the pin length. This gives the total volume of material lost, which is divided by the area of the circle to obtain the average wear rate, and then divided by the weld length to give the wear rate per meter of weld.
[0204] For clarity, ideally all proportional calculations are done using base SI units, which are based on meters and seconds rather than any other sub-units such as mm and μm, but the scaling of parameter values in the field makes this impractical. Therefore, throughout the specification, the following units are used:
[0205] Pin length L in mm
[0206] Wear in μm
[0207] Wear rate (WR) in μm / m
[0208] Wear rate ratio (WRR) in μm / (m.mm)
[0209] The rotation rate in cycles per minute
[0210] The wear rate of the tool may increase significantly as the tool wears, since the interaction between the tool and the workpiece may become less effective. The wear rate may also be artificially high initially if there is any surface damage introduced into the tool by the process used for forming (e.g., by grinding). Furthermore, to ensure sufficient wear to measure accurately, wear needs to be measured over a certain number of meters of weld at the low levels of wear envisioned in this specification. Wear will not be significantly affected by the number of penetrations, as long as this number remains reasonable.
[0211] Therefore, a minimum weld length of 9.5 m (e.g., nominally 10 m) is required (D W) and typically less than 35m (however this is only a practical limit), using no more than 1 tool insertion per 1.8m of weld, and where if there is any evidence of significantly accelerated wear initially, a nominal 2m (at least 1.8m and less than 2.2m) of pre-test welding is completed prior to the main wear measurement to remove the surface layer of the tool.
[0212] In FSW, the main driving forces are weld quality and tool life. These are directly linked, because the operating conditions in which the workpiece area (welding area) around the tool becomes too hot cause excessive chemical wear of the tool and thermal tearing in the weld zone, resulting in poor welding. On the contrary, operation when the welding area is too cold causes poor plasticity, has high forces on the tool, may cause fractures and produce voids in the weld. In addition, slowing down the traverse rate can reduce the lateral force on the tool, but because the rotational resistance is dominant, they will not significantly reduce the wear rate, but will increase the residence time in the workpiece, which will increase chemical wear. Therefore, the conditions for optimal welding are basically the same as those for minimum tool wear. The above welding parameters provide a good starting point for establishing welding, however, they may need to be changed to optimize the welding process and minimize the wear rate (per meter) on the tool.
[0213] The wear rate of interest is then the minimum wear rate (WR) achieved using the exact conditions given above or conditions optimized from them. M ), which provides good quality welds without voids and hot tearing. The material of the present invention has an average wear rate ratio of less than 1.0 μm / (m.mm) and preferably less than 0.5, 0.2, 0.1, 0.05 μm / (m.mm).
[0214] Existing technology and test tools for 6mm welding
[0215] Most prior art publications report testing of tools suitable for 6mm welding and show significant wear on the tool after 30m, so that the main feature of the spiral on the tool is completely lost at the pin base. From images of these tools, it is possible to estimate all material loss within a circle with the pin length as diameter and from this calculate an approximate wear rate for comparison, with values for 6mm tools being >20μm / m wear rate, giving a wear rate ratio of >3. In contrast, the tool inserts of the present invention show wear rates of around 0.05.
[0216] Scaling between tool sizes
[0217] Performance testing is most conveniently done on tools designed for 6 mm welding, but it is important that the results can be scaled to other tool sizes. Scaling is primarily based on empirical observations, however this can be supported in some cases by the application of analytical methods. Computational modeling is also being developed for the FSW process, but is generally not yet sufficient to predict all aspects of welding. Therefore, ultimately empirical observations are the most important contributors to the model at this time. It is also often found that the mechanical design or shape of the tool insert can be simply scaled from the design of the 6 mm tool in order to achieve similar results. Therefore, a single design and knowledge of the dimensions of a specific defined feature is sufficient. For convenience, this feature is considered to be the pin length L; in practice, it is also used as the basic proportional length.
[0218] The key variables in FSW are therefore (in standard SI units throughout):
[0219] L = Pin length (m)
[0220] ν=traverse speed (m / s)
[0221] ω = rotational speed of the tool
[0222] Three forces are applied to drive this behavior.
[0223] F A =Axial load (N)
[0224] F T = Transverse force (N)
[0225] F R = Rotational force (N·m)
[0226] The work done on the workpiece (causing heating) is mainly produced by the rotational force and is generated by F R ·ω is given. In principle, the additional heating comes from F T ·ν, but this is usually much smaller, and the axial force F A No work is done because all movement is perpendicular to the force.
[0227] Parametric Model
[0228] The standard set of test parameters for 6mm tools is:
[0229] D W =6mm
[0230] L=0.95D W (1)
[0231] L = Pin length (m) = 0.0057m (5.7mm)
[0232] ν=traverse speed(m / s)=0.005m / s (0.3m / min)
[0233] ω = tool rotation rate = 200 rpm
[0234] And the forces that achieve this are typically:
[0235] F A =Axial load (N) = 3800N (3.8kN)
[0236] F T = Transverse force (N) = 1000N (1kN)
[0237] F R =Torque (N·m) =To be confirmed
[0238] Typically, the traverse rate is inversely proportional to L, such that:
[0239] L·ν=constant=2.85*10 -5 m 2 / s(2)
[0240] Therefore, if L is doubled for an application where DW = 12 mm, the traverse rate will typically be halved to 0.0025 m / s.
[0241] Typically, the tool rotation rate ω is approximately:
[0242] ω=ω 6 L / L 6 ^(1 / 3) (3)
[0243] The subscript 6 refers to the value of the parameter for a welding depth of 6 mm.
[0244] The force also scales approximately as L^(3 / 2).
[0245] These relationships enable one skilled in the art to appropriately configure initial test parameters for tool sizes in the range of 2 mm - 30 mm, and from these initial values optimize the test to achieve low wear rates of the tool inserts.
[0246] Ultimately, there is no benefit to having a minimum wear rate, and while a zero wear rate would not be natural, there is no obvious way to predict what the minimum wear rate might be. For practical purposes, there is a practical threshold that can be measured, i.e. if the test is limited to 30m and the measurement of mean wear is limited to 5μm, then a practical lower limit for the measured wear rate is 0.17μm / m weld. Therefore, in some embodiments, there is a preferred lower limit of 0.17μm / m wear.
[0247] One skilled in the art will be able to determine the wear rate and penetration life of any given FSW tool using the procedures presented herein.
[0248] Grain sharpness measurement
[0249] Follow these steps:
[0250] -Convert the image to 8-bit grayscale
[0251] -Using thresholding technique, identify cBN grains within 0-255 grayscale.
[0252] - Binarize the image
[0253] - Use Watershed image processing technology to separate grains
[0254] - Use software to calculate the area and perimeter of the grains.
[0255] - Use the following expression to determine circularity, i.e. the sharpness of the grains:
[0256]
[0257] While the invention has been particularly shown and described with reference to embodiments, it will be understood by those skilled in the art that various changes in form and details may be made without departing from the scope of the invention as defined by the appended claims.
Claims
1. A polycrystalline cubic boron nitride (PCBN) composite material, comprising: 60-90 volume % cubic boron nitride cBN particles and 10-40 volume % of a binder matrix material, wherein the cBN particles are dispersed in the binder matrix material, wherein the cBN particles have an average grain size in the range of 8 to 20 μm, wherein the binder matrix material comprises an alloy of refractory metals tungsten (W) and rhenium (Re) at 90-98 weight %, and wherein the binder matrix material further comprises aluminum (Al) in non-oxide form, wherein the binder matrix material comprises an interface layer on the cBN grains, wherein the interface layer is a reaction layer comprising Al, B and N, and wherein the interface layer comprises aluminum nitride and / or aluminum boride, wherein the aluminum (Al) is present in an amount of 2-10 weight % of the binder matrix material, and wherein the interface layer has an average thickness in the range of 100-250 nm.
2. The PCBN composite material according to claim 1, wherein the interface layer covers at least 50% of the surface of the cBN grains.
3. The PCBN composite material of claim 1, wherein the composition of the reaction layer varies throughout its thickness.
4. The PCBN composite material according to claim 1 or 2, wherein the average thickness of the interface layer containing Al is 170-190 nm.
5. The PCBN composite material according to claim 1 or 2, wherein the total oxygen content of the PCBN composite material is less than 3%.
6. The PCBN composite material according to claim 1 or 2, wherein the total oxygen content of the PCBN composite material is less than 2%.
7. The PCBN composite material according to claim 1 or 2, wherein the total oxygen content of the PCBN composite material is less than 1%.
8. The PCBN composite material according to claim 1 or 2, wherein the total oxygen content of the PCBN composite material is less than 0.5%.
9. The PCBN composite material according to claim 1 or 2, wherein the total oxygen content of the PCBN composite material is less than 0.3%.
10. The PCBN composite material according to claim 1 or 2, comprising 65-75 volume % of cBN particles and 25-35 volume % of a binder matrix material.
11. The PCBN composite material according to claim 1 or 2, wherein the composition of the W-Re alloy lies in the following range: 72 wt% to 77 wt% of tungsten (W) and correspondingly 23 wt% to 28 wt% of Re.
12. The PCBN composite material according to claim 1 or 2, wherein the grains of the W-Re alloy have an average grain size in the range of 3 to 5 μm.
13. The PCBN composite material according to claim 1 or 2, further comprising WC impurities within the binder matrix material, the WC impurities being present in an amount less than 1 wt% of the PCBN composite material.
14. The PCBN composite material according to claim 1 or 2, further comprising a rhenium-aluminum alloy in the binder matrix material.
15. The PCBN composite material according to claim 1 or 2, wherein the cBN particles have a sharpness ranging from 0.40 to 0.
70.
16. The PCBN composite material of claim 1 or 2, having a Young's modulus of 500 to 560 GPa, derived using the sonic velocity method.
17. The PCBN composite material according to claim 1 or 2, having a sonic velocity of 8 to 9 km / s.
18. A method for manufacturing the polycrystalline cubic boron nitride (PCBN) composite material according to claim 1, the method comprising the following steps: Providing a matrix precursor powder comprising refractory metals tungsten (W) and rhenium (Re) and further comprising 2 to 10 wt % of Al in non-oxide form; Providing cubic boron nitride (cBN) powder comprising cBN particles; mixing matrix precursor powder and cBN powder; compacting the mixed matrix precursor powder and cBN powder to form a green body; degassing the green body at a temperature of 800°C to 1150°C; The green body is sintered at a temperature of 1300° C. to 1600° C. and a pressure of at least 3.5 GPa to form a PCBN composite material according to claim 1 .
19. The method according to claim 18, wherein the PCBN composite material is as described in any one of claims 2 to 17.
20. The method of claim 18 or 19, wherein the matrix precursor powder comprises separate particles of W, Re and Al.
21. The method of claim 18 or 19, wherein the matrix precursor powder comprises particles having both W and Re, the W and Re being pre-alloyed or as separate phases.
22. The method of claim 18 or 19, wherein the mixing step comprises mixing the matrix precursor powder and the cBN powder using a mixing container that does not contain exposed metal or WC surfaces.
23. The method of claim 18 or 19, wherein the mixing step comprises mixing the matrix precursor powder and the cBN powder in a polymer or polymer coated mixing tank.
24. The method according to claim 18 or 19, wherein the mixing step comprises the following sub-steps: Add cBN and aluminum powders together; Mix in a container at 800 rpm for 2 minutes, then at 1200 rpm for 2 minutes; Add half of the tungsten-rhenium powder to the cBN and aluminum powders; Mix in a container at 800 rpm for 2 minutes, then at 1200 rpm for 2 minutes; adding the remaining half of the tungsten-rhenium powder to the cBN and aluminum powders; and Mix in the container at 800 rpm for 2 minutes and then at 1200 rpm for 2 minutes.
25. The method of claim 18 or 19, wherein the sintering step comprises sintering at a temperature of 1500°C.
26. The method of claim 18 or 19, wherein the sintering step comprises sintering at a pressure in the range of 4.0-6.0 GPa.
Citation Information
Patent Citations
A tool assembly for friction stir welding
GB201819835D0
Apparatus and method for friction stir welding of high strength materials, and articles made therefrom
US20040238599A1
Improvements relating to friction welding
WO1993010935A1
Applications of friction stir welding using a superabrasive tool
WO2004101205A2
Tungsten rhenium compounds and composites and methods for forming the same
CN102016087A